Property Development Risk Analysis Mandalika Resort Lombok Tourism Area - Muka, I Wayan (IPTEK Journal of Proceedings Series, 2017)
The role of the property sector to the national economy is very important. Not only its role in absorbing labor but also contributions to improving national economic growth. Great relevance to other sectors of the economy also makes the property sector requires strict protection and supervision of various parties, especially the government. It aims to prevent systemic risk due to the fall of the property sector to other economic sectors. Risks and uncertainties always occur in property development. The risk of an effect on every stage of the process of the development of ideas, feasibility studies, commitment to the construction and operation phase. The risk management process is generally a continuous and iterative process, even every kind of development is different and unique properties. This study aims to identify sources of risk, risk factors, the level of hazard, vulnerability level, the level of capacity and determine the priority risks in property development process. Steps being taken in this study include: the identification of sources of risk, the stage of identification of risk factors, the stage of identification of the level of hazard, the stage of identification of the level of vulnerability, the stage of identification of the level of capacity, the stage of risk analysis and risk priority index ( IPR). Conceptually, the proposed method in this study refers to the key measures of risk management that includes identification, qualitative risk analysis in the process of property development. Data collected through interviews and questionnaires by resource persons involved in property development in the tourism area Mandalika Resort Lombok in West Nusa Tenggara Province. Results of research on the development of the area Mandalika Resort Lombok can be concluded that the stages of development that are most at risk is the stage of an idea (IPR = 0.152), followed by the stage of feasibility (IPR = 0.067), then the commitment stage (IPR = 0,036), construction (IPR = 0.026) and stage management (IPR = 0.010). The results of this assessment indicate that the idea stage is the stage of development of the property are recommended to get treatment or priority risk response. Concluded the process of property development in the region Mandalika Resort Lombok is not worth continuing before risk mitigation that is unacceptable